Surgical Approaches to Supradiaphragmatic Segment of IVC and Right Atrium through Abdominal Cavity during Intravenous Tumor Thrombus Removal - Dmytro Shchukin; Vladimir Lesovoy; Igor Garagatiy; Gennadiy Khareba; Redouane Hsaine (Advances in Urology)
Objective. The purpose of this study was to investigate safety and feasibility of some surgical approaches to the supradiaphragmatic inferior vena cava (IVC) and the right atrium through the diaphragm from the abdominal cavity. Materials and Methods. The material of the anatomical study included 35 fresh cadavers. Several options of surgical access to the supradiaphragmatic IVC were successively performed. Feasibility and risk level of each of the approaches were evaluated with the use of a special scale. Results. The isolation of the supradiaphragmatic IVC and cavoatrial junction was most easily performed via T-shaped or circular diaphragmotomy (grade “easy” was registered in 74.3% and 80% of patients, resp., compared to 31.4% for transverse diaphragmotomy and 40% for isolation of the IVC in the pericardial cavity). The risk analysis has demonstrated the highest safety level for T-shaped diaphragmotomy (grade “safe” was registered in 60% of cases). The intervention via transverse diaphragmotomy, circular diaphragmotomy, and IVC isolation in the pericardial cavity was graded as “risky” in 80%, 62.9%, and 82.9% of cases, respectively. Conclusions. In our opinion, T-shaped diaphragmotomy is the most safe and easy-to-perform access for mobilization of the supradiaphragmatic IVC through the abdominal cavity.